The Ukraine war and its food security implications in Sri Lanka - Thibbotuwawa, Manoj; Dissanayake, Nimesha; Niwarthana, Sachini (International Food Policy Research Institute, 2023)
The Ukraine War has had major implications for food security and food systems across the world given the important role both Russia and Ukraine play in global food, fertilizer, and energy markets. Russia and Ukraine together supply about 12% of global agricultural exports on a caloric basis and over 30% of global wheat exports.1 Fertilizer and energy markets experienced rising prices and supply disruptions as well. The Russia-Ukraine conflict heavily impacted food security in Sri Lanka which is dependent on imports from the Caspian region. The impact of this shock has been compounded for Sri Lanka which has been suffering from a severe economic crisis due to a lack of foreign reserves, a debt default, high inflation, import restrictions, and shortages of critical goods and services. These compound crises have halted Sri Lanka’s progress on economic development and its achievement of the SDGs. Progress had been significant with the share of undernourished population declining from 16.7% in 2001 to 3.4% in 2020.2 During the same period the prevalence of stunting declined from 20.6% to 16%.3 The prevalence of wasting among children under age five declined from 15.9% in 2000 to 15.1% in 2016. Sri Lanka was ranked 65th out of 116 countries on the Global Hunger Index and 77th out of 113 countries on the Global Food Security Index in 2022 suggesting the need for some improvements in the food system. The latest food security assessment by the World Food Program (WFP) notes that about 30% of the population of 22 million (6.26 Mn people) are food insecure.4 Further, most households are regularly employing food-based coping strategies such as eating less preferred and less nutritious food and reducing the amount of food they eat. Further, an estimated 200,000 households are using emergency livelihood coping strategies that are likely to severely impact their income-generating activities and it is anticipated that more people are turning to these coping strategies as the crisis deepens. Against this backdrop, this policy brief explores the impacts of the evolving crisis in Ukraine on the nexus of poverty, agriculture, and food security in Sri Lanka and the possible avenues for mitigating the negative implica-tions of export restrictions, rising import costs, and inflation.